THE IMPLEMENTATION OF ISLAMIC EDUCATION VALUES IN THE LOCAL WISDOM OF THE JAVANESE SEDEKAH BUMI TRADITION - Bambang Yuniarto; Rizqo Anis Safitri, Asep Palahu Rijal, Andriana, Saffiyah Ummu Zainab (Indonesian Journal of Education (INJOE), 2023)
The earth alms ceremony it self is a tradition carried out by Javanese people in the Cirebon, Indramayu and Brebes regions at the beginning of Muharram or Shura. The Earth Alms tradition is held as a form of gratitude to the Almighty Allah SWT who has provided a place to stand with all the abundant sustenance in the form of crops for human survival. Sedekah Bumi is generally held in public places that are considered sacred such as the courtyard of the mosque, village hall, or field. Values in life become the basis or reference in determining an action. Value has a positive connotation because value is something that is used as a basis and agreed upon and has a positive impact on both self and others such as the value of honesty, responsibility, helping and other values. This type of research uses a qualitative approach in the form of an analytical descriptive method or research supported by data obtained from field research.